Evolution of the objectives of eradication of extreme poverty and inequality in Colombia (2020)
The issue of poverty and inequality is discouraging based on the little concern on behalf of the Presidential candidates regarding the strengthening of strategies and policies aimed at improving and reducing this indicator, which is why it is necessary to examine and analyze the causes of this phenomenon, from the perspective of macroeconomic policy, the concentration of income and wealth, corruption, and the lack of coordination of territorial and district entities. Establish what have been the economic and social implications which make it impossible to achieve economic growth; rethink the orientation of the economy; refocusing the policies and strategies used by the Government to improve the quality of life of people.